EDUKASI MINAT BUDAYA LITERASI UNTUK ANAK-ANAK DESA SUKAHARJA - Muhammad Restu Rojudin; Muhajir Affandi (JPMUJ, 2025)
In this study I will discuss the urgency of the cultural development of literacy for the children of sukaharja village. The purpose of this writing is for children of an early age to learn the extent of the importance of literacy culture's early application. And it can also support applications of national literacy movements. As it is known that the literacy in Indonesia has been reduced in proportion to other countries. Indonesia already ranked 64th from 65 countries in 2012. For this reason it should be recognized the importance of reading early on, because reading is able to know of knowledge that has no boundaries. The study USES qualitative methods with an open reading site. It will show from this study that a literary culture is desperately needed for recognition and has been embedded at an early age. Through this program, I hope that parents or especially children can open up new insights into science through reading. Because also books are a window to the world.